Defining and Redefining U.S.-Africa Trade Relations During the Trump Presidency. (27th November 2017) - Lande, Stephen; Matanda, Dennis
Abstract : In an era in which multilateral trade arrangements have garnered more public notoriety than ever before, the suboptimal trade and investment relationship between America and Africa, as underpinned by the African Growth and Opportunity Act (AGOA), is one of the less controversial ones. AGOA could nevertheless use some adjustments or augmentations to facilitate deeper U.S.-Africa commercial relations. For instance, adjusting AGOA's origin rules could nudge the private sector on both sides of the Atlantic towards gains for U.S. and African employment and the reduction of trade deficits. Africa must leverage the period before AGOA expires to redefine its trade relationship with the United States in innovative ways. The United States should welcome these measures, since the type of value that Africa would add to the global supply chain would not replace the high-quality jobs that the Trump Administration would like to see in the United States. In fact, this type of production would make U.S. manufacturing more competitive.